Pioglitazone, a Peroxisome Proliferator-Activated Receptor-γ Agonist, Downregulates the Inflammatory Response in Cutaneous Leishmaniasis Patients Without Interfering in Leishmania braziliensis Killing by Monocytes - Nascimento, Maurício T.; Cordeiro, Ravena S. O.; Abreu, Cayo; Santos, Camila P.; Peixoto, Fábio; Duarte, Gabriela A.; Cardoso, Thiago; de Oliveira, Camila I.; Carvalho, Edgar M.; Carvalho, Lucas P. (Frontiers in Cellular and Infection Microbiology, 2022)
Patients with cutaneous leishmaniasis (CL) due to Leishmania braziliensis infection have an exacerbated inflammatory response associated with tissue damage and ulcer development. An increase in the rate of patients who fail therapy with pentavalent antimony has been documented. An adjuvant therapy with an anti-inflammatory drug with the potential of Leishmania killing would benefit CL patients. The aim of the present study was to investigate the contribution of peroxisome proliferator-activated receptor-γ (PPAR-γ) activation by pioglitazone in the regulation of the inflammatory response and L. braziliensis killing by monocytes. Pioglitazone is an oral drug used in the treatment of diabetes, and its main mechanism of action is through the activation of PPAR-γ, which is expressed in many cell types of the immune response. We found that activation of PPAR-γ by pioglitazone decreases the inflammatory response in CL patients without affecting L. braziliensis killing by monocytes. Our data suggest that pioglitazone may serve as an adjunctive treatment for CL caused by L. braziliensis.